Improving the chloride binding capacity of cement paste by adding nano-Al2O3: The cases of blended cement pastes. (30th January 2020) - Yang, Zhiqiang; Sui, Shiyu; Wang, Liguo; Feng, Taotao; Gao, Yun; Mu, Song; Tang, Luping; Jiang, Jinyang
Highlights: NA can be used as reactive alumina resource in cement paste. Influence of NA on the chloride binding capacity of blended cement pastes were investigated. NA is beneficial for improving the chloride binding capacity of cement paste blended with SCMs. Abstract: Chloride ingress is one of the main causes for the degradation of reinforced concrete structures. Increasing the chloride binding capacity of concrete is generally thought as a feasible way to restrain the chloride ingress. In our previous study, the γ-phase nano-Al2 O3 (NA) was found to be beneficial for improving the chloride binding of plain Portland cement paste as a result of the formation of additional Friedel's salt. Herewith, the cases of blended cement pastes were further investigated, into which supplementary cementitious materials (SCMs) were incorporated, including fly ash (FA), blast furnace slag (SL) and silica fume (SF). NA with a dosage of 1% and 2% was introduced to blended cement paste, and the chloride binding capacity of which were determined with the conventional equilibrium method. The results showed that the use of NA was even viable to improve the chloride binding capacity of blended cement pastes. X-ray diffraction (XRD)/Rietveld refinement method and thermogravimetric analysis (TGA) were performed to unravel the phase assemblages change upon exposure. It was revealed that besides the formation of more Friedel's salt, the addition of NA could allow the enhanced physical binding of chloride as a result of the formation of C-A-S-H, i.e., the substitution of Si by Al in C-S-H gel.